Культурные мотивы в польском переводе „Куда ж нам плыть?” Б. Акунина - Jolanta Jóźwiak (Studia Rossica Posnaniensia)
The aim of the paper is to present the results of translators’ individual choices in the process of conveying cultural-background elements to the target culture. The source material were taken from novel Where shall we go? by Boris Akunin and its translation into Polish. The possibility of transferring specific values such as cultural connotation is discussed in the context of potential readers’ reactions.